A new species of callianassid ghost shrimp of the genus Nihonotrypaea Manning & Tamaki, 1998 (Crustacea, Decapoda, Axiidea, Callianassidae) from southern part of the Russian coast of the Sea of Japan - Marin, Ivan (Zootaxa, 2013)
A new species of callianassid shrimp genus Nihonotrypaea Manning & Tamaki, 1998 (Crustacea: Decapoda: Axiidea: Callianassidae) is described from the Peter the Great Bay, Primorye, Russian coast of the Sea of Japan. The species clearly differs from other representatives of the genus by unique armature of ventral margin of merus and different form of carpus of major cheliped in males and yellow-greenish coloration never observed in other species of the genus Nihonotrypaea.